Journalism, Power and Investigation : global and activist perspectives - Price, Stuart, 1958- (London : Routledge, 2019)
"Journalism, Power, and Investigation presents a contemporary, trans-national analysis of investigative journalism. Beginning with a detailed introduction that examines the relationship between this form of public communication and normative conceptions of democracy, the book offers a selection of spirited contributions to current debates concerning the place, function and political impact of investigative work. The fourteen chapters, produced by practicing journalists, academics, and activists, cover a range of topics, with examples drawn from the global struggle to produce reliable, in-depth accounts of public events. The collection brings together a range of significant, present-day investigations from across the world. These include an assignment conducted in the dangerous sectarian environment of Iraq, a close engagement with Spain's Memory Movement and the work of radical charity Global Witness. Chapters also examine the troubled political legacy of Wikileaks, legal constraints on investigative journalism in the UK and the bold international agenda of the investigative collective the Ferret. This is alongside other analytical pieces on events in Bermuda, Brazil, and Egypt. Investigative journalism is a form of reportage that has long provided a benchmark for in-depth, critical interventions. Along with case studies, Journalism, Power and Investigation gives students and researchers an insight into the principles and methods that animate this global search for truth and justice"--
Introduction: journalism, democracy and the critique of political culture / Stuart Price -- Investigative journalism and terrorism: the proactive legal duty to report / Richard Danbury -- Researching the deep state: surveillance, politics, and dissent / Ben Harbisher -- State, hierarchy and executive power: journalists under duress / Stuart Price -- Can you keep a secret? legal and technological obstacles to protecting journalistic sources / Richard Danbury and Judith Townend -- Overview -- Citizens' investigations: recovering the past in contemporary Spain / Ruth Sanz Sabido -- Global witness and investigative journalism / Ali Hines -- Violence and impunity in Rio de Janeiro's favelas: citizens, smartphones and police malpractice / Fernanda Amaral -- Surviving the sectarian divide: investigative journalism in the quagmire of Iraq / Ahmed Bahiya -- Co-operative international coverage: the Ferret's foreign reporting / Peter Geoghegan, Billy Briggs and Brindusa Ioana Nastasa -- After the Arab revolts: social media and the journalist in Egypt / Zahera Harb Birks -- Protecting the colony: Bermuda's national image and media censorship / Dana Selassie -- Fact-checking, false balance and "fake news": the discourse and practice of verification in political communication / Jen Birks -- Wikileaks and investigative journalism: the organization's effects and unfinished legacy / Lisa Lynch -- Online news video, collaboration and social networks: the disruption of the media industry / David Hayward.
Includes bibliographical references and index.
Keywords: Investigative reporting